(untitled) (Global Journal of Human-Social Science, 2017)
This paper investigates comparatively the critical nature of infrastructure to the overall development of nations. It points out that critical infrastructure decay in Nigeria is directly related to major issues of development crises in Nigeria. The methodology adopted for this paper is basically content analysis while making use of secondary data in comparative analysis. The paper tries to find answers to the issues of critical infrastructure decay i.e epileptic power supply, poor road network and transportation/ communication imbalances, failing educational structure, overall unemployment, the disconnect between public and private sectors in sustainable infrastructural development, etc in Nigeria. The paper concludes that critical infrastructure must not be treated with levity and neglect if the nation must break out the dialectical cycle of development crises.